O caranguejo aratu chega à universidade: a história em quadrinhos como estratégia didática na aprendizagem de ciências e na formação de professores - Pessoa, Camylla Alves do Nascimento (2015)
This study is in line Education, Curriculum and Teaching, on Axis of Sciences, the Graduate program in Brazilian Education, Federal University of Ceará. This essentially the HQ of the contribution as a teaching strategy in learning scientific concepts in the training of elementary school science teachers. Has the objective to analyze the influence of comics in understanding science concepts and as a teaching strategy in the training of science teachers in the early years of elementary school. The research is characterized by qualitative approach, descriptive and explanatory typology. To collect data, a questionnaire was administered to undergraduates pedagogy course of a public university in the state of Ceará, students of the discipline science education, to understand personal aspects of the design of these students on the HQ and the possibilities of its use in learning of scientific concepts and also diagnose the prior design of future teachers on the characteristics of the mangrove ecosystem. Two focus groups were conducted to identify the possible influence of the comic strip "Mangueando: life in Lama" in the design of undergraduates on the concepts related to mangroves, which also allowed to know the opinion of future teachers about the use of this strategy in Education Superior. Data were analyzed using content analysis based technique Bardin (2011), and took place in three stages: pre-analysis; exploration of the material; the processing of results and interpretation. To analyze the data was chosen category analysis through thematic units of record. Considering the analyzes it can be seen that the HQ has several benefits to the process of teaching and learning, they show the concepts of interesting and entertaining way. Regarding the teaching of science, the advantages of this strategy have been identified to provide the formation of a critical consciousness in readers and also revealed the potential of this resource to introduce concepts and attitudes aimed at preserving the environment. For higher education, student teachers reported positive rich interaction possibilities of this strategy with the learning of scientific concepts. Finally, this study found evidence that the “HQ: Mangueando: life in Lama” contributed to the expansion of the design of future teachers about the mangrove characteristics, which included soil, flora and fauna, which can aid in the preservation of this so valuable ecosystem.